Educational Psychology Review - Paas, Fred.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Educational Psychology Review is an international forum for the publication of peer-reviewed integrative review articles, special thematic issues, reflections or comments on previous research or new research directions, interviews, replications, and intervention articles - all pertaining to the field of educational psychology. All publications provide breadth of coverage appropriate to a wide readership in educational psychology and sufficient depth to inform specialists in that area.
Keywords: Learning; Instruction; Educational psychology; Education -- Psychology; Child psychology; School psychology; Educational Psychology; Child and School Psychology; Learning and Instruction